Nonaneurysmal Subarachnoid Hemorrhage in Sickle Cell Disease: Description of a Case and a Review of the Literature. Issue 4 (July 2018) - Zuccoli, Giulio; Nardone, Raffaele; Rajan, Deepa; Khan, Abdullah S.; Cummings, Dana D.
Abstract : Descriptions of the natural history of cerebrovascular complications of sickle cell disease (SCD) characterize ischemic stroke as common during childhood and hemorrhagic stroke as more common in adulthood. Childhood ischemic stroke is attributed to vasculopathy with moyamoya syndrome. Hemorrhagic stroke is commonly attributed to aneurysms accompanying HbSS cerebral vasculopathy in SCD. However, a growing body of literature highlights multiple contributing factors to hemorrhagic stroke in children. Primary hemorrhagic stroke is one of the most devastating neurological complications of SCD. We describe the case of an 18-year-old female affected by HbSS genotype SCD presenting with reversible cerebral vasoconstriction syndrome (RCVS) as well as features of posterior reversible encephalopathy syndrome and convexity subarachnoid hemorrhage (SAH) after transfusion of red blood cells. We reviewed the existing literature dealing with SCD, blood transfusion, and hemorrhagic strokes. To our knowledge, this case presentation is unique with convexity SAH predominantly attributable to a RCVS spectrum disorder occurring in the setting of a recent blood transfusion in an adolescent female with SCD. As this case illustrates, neurological deterioration accompanied by intracranial hemorrhage in children and young adults with SCD after blood transfusion should raise suspicion for RCVS as part of a complex cerebral vasculopathy. A better understanding of the risk factors leading to hemorrhagic stroke may help prevent this severe complication in subjects with SCD. Neuroimaging including angiography in these subjects may enable prompt diagnosis and management.